2018
DOI: 10.1029/2017ja024920
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Controlled Density Structures in the Martian Ionosphere: Are they Stably Recurring?

Abstract: MARSIS instrument aboard the Mars Express spacecraft regularly detects the magnetically controlled density structures (MCDSs) in the Martian ionosphere. In this paper, we studied the recurrence characteristics of these MCDSs using long‐term (more than a decade) MARSIS observations over a selected region of 35° to 40° longitude and −10° to 10° latitude, where a strong magnetic anomaly is present. Instead of a conventional echogram analysis, we used the peak density echogram analysis as the latter is able to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 30 publications
5
14
0
Order By: Relevance
“…In Figure , the simulated echograms (black lines) are overplotted with the corresponding echograms of orbit 4447. The simulated echograms at frequencies of 3 and 3.5 are well fitted with the respective echograms observed on orbit 4447, in accordance with the previous simulations (Duru et al, ; Mohanamanasa et al, ). The simulated echogram at 4.5 MHz also correlates well with the observed one, suggesting that the assumed density structures are appropriate ones.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In Figure , the simulated echograms (black lines) are overplotted with the corresponding echograms of orbit 4447. The simulated echograms at frequencies of 3 and 3.5 are well fitted with the respective echograms observed on orbit 4447, in accordance with the previous simulations (Duru et al, ; Mohanamanasa et al, ). The simulated echogram at 4.5 MHz also correlates well with the observed one, suggesting that the assumed density structures are appropriate ones.…”
Section: Resultssupporting
confidence: 89%
“…The above analysis suggests that the enhanced densities are in fact the MCDS of the type reported earlier (Andrews et al, 2014;Diéval et al, 2015;Duru et al, 2006;Gurnett et al, 2005;Mohanamanasa et al, 2018) but occur at very low altitudes. By considering these characteristics, the shapes of the density structures that are responsible for the observed electron densities are illustrated through a schematic diagram in Figure 4.…”
Section: 1029/2018ja026400supporting
confidence: 68%
See 2 more Smart Citations
“…It is therefore possible that the density structure squeezed between two consecutive ionograms. It is also interesting to note that—although apparently quite stable features (Andrews et al, ; Mohanamanasa et al, )—such density structures have not been so far observed in the local electron density data obtained by the Mars Atmosphere and Volatile EvolutioN Mission spacecraft. This seems to be consistent with very small dimensions of these structures suggested by our analysis.…”
Section: Discussionmentioning
confidence: 96%